The importance of being seen to be Green: an empirical investigation of Green Marketing Strategies in Business-to-Business organizations - Berth, Nicole (Auckland University of Technology, 2011)
The purpose of this dissertation is to define Factors of Greenness for Business-to-Business organizations in order to define and operationalize the Greenness Matrix of Simula, Lehtimäki and Salo (2009). Operationalization refers to the definition of a vague concept aiming to make that concept measurable and useable for companies and academics (Bryman & Bell, 2007).The research differs from other research in the marketing discipline as no research has addressed the definition of Greenness Factors in B2B organizations. This research defines those Greenness Factors with empirical support of manufacturers and business buyers operating in the chemical sector. To start off, the research reviews the concepts of sustainability and green marketing. A successful green marketing strategy needs to include sustainability in order to satisfy the buyer’s needs and expectations (Charter et al., 2002). Sustainability is outlined from a marketing perspective and relevant literature in Business-to-Customer and B2B marketing is presented. The concept of green marketing is outlined and differentiated from sustainability. This research looks at B2B organizations. Therefore, it is outlined why green marketing particularly benefits B2B organizations which justifies the area studied. The research then moves on to uncover the link between both concepts and the studies that incorporate sustainability and green marketing focussing on B2B organizations. As one of those studies, the Greenness Matrix of Simula et al. (2009) is introduced as a basis for this research. It suggests that B2B organizations must consider their actual greenness in comparison to the perceived greenness of their business buyers. But Simula et al. (2009) fail to define high or low greenness which makes it impossible for B2B organizations to implement greenness. This research will define Greenness Factors to identify what makes-up high or low greenness from a manufacturer’ and business buyer’s perspective. A thematic analysis of interviews with manufacturers and business buyers in the B2B environment is conducted. Five super themes are identified which are labelled as Greenness Factors. In developing the Greenness Factors, the Greenness Matrix (Simula et al., 2009) can be operationalized to assist B2B organizations to implement greenness to facilitate future research in the area. Findings discover the philosophy of a company as the most significant Greenness Factor as it is crucial to the effectiveness of a green marketing strategy. It further strongly influences the other Greenness Factors in their orientation of being high or low.
Keywords: Green Marketing; Business-to-Business; Sustainability